Public mental health during and after the SARS-CoV-2 pandemic: Opportunities for intervention via emotional self-efficacy and resilience - Karnaze, Melissa M.; Kious, Brent M.; Feuerman, Lindsay Z.; Classen, Sarah; Robinson, Jill O.; Bloss, Cinnamon S.; McGuire, Amy L. (Frontiers in Psychology, 2023)
During the pandemic, the number of US adults reporting clinically significant symptoms of anxiety and depression sky-rocketed from 11% in 2020 to over 40% in 2021. Our current mental health care system cannot adequately accommodate this crisis. Therefore, it is important to identify opportunities for public mental health interventions and assess whether modifiable psychological factors may offer an intervention point. In January 2022, adults living in the U.S. were recruited via Amazon Mechanical Turk to complete an anonymous survey. Linear regressions tested whether the primary outcomes (depressive and anxiety symptoms, burnout) were associated with hypothesized modifiable risk factors (loneliness and need for closure) and hypothesized modifiable protective factors (ability to perceive emotions and connect with others emotionally, emotion regulation efficacy, resilience). The sample included 1323 adults, almost half of whom reported clinically significant depressive and/or anxiety symptoms, 90% indicated feeling burned out at least once a year, and 45% felt burned out once a week or more. Depressive and anxiety symptoms and burnout were statistically significantly associated with loneliness, need for closure, recent stressful life events, and resilience. Depressive and anxiety symptoms were associated with emotional self-efficacy and beliefs about the malleability of emotions. Associations between loneliness and symptoms were weaker among those with more emotional self-efficacy, emotion malleability beliefs, and resilience. Public mental health interventions that teach resilience in response to negative events, emotional self-efficacy, and emotion regulation efficacy may protect against the development of depressive symptoms, anxiety, and burnout, particularly in the context of a collective trauma.